FAKTOR - FAKTOR YANG MEMPENGARUHI KEMAUAN WAJIB PAJAK MENJADI PESERTA AMNESTI PAJAK - Yani, Dina Ambara; Noviari, Naniek (E-Jurnal Akuntansi, 2017)
The most inland revenue financed by taxes. The realization of the State Budget does not meet national development targets. One of government effort to overcome this issue is by promote Tax Amnesty Programme. The purpose of this study is to see the influence of knowledge and understanding of the tax amnesty law, a good perception on the tax amnesty system, the credibility level of legal system and law on the taxpayer’s willingness to be tax amnesty participant. The sample is determined by incidental sampling method with a sample size of 100 individual taxpayers registered at the Tax Office Primary Gianyar. Methods of data collection using questionnaires. Data analysis technique used is multiple linear regression analysis. The results of this study the knowledge and understanding of regulations tax amnesty, and a good perception on the tax amnesty’s system has the positive effect on the willingness of taxpayers participated in tax amnesty While the credibility level of legal system and law has no effect on the willingness of the taxpayer participated in a tax amnesty.
Keywords: Knowledge and understanding of the tax amnesty law, a good perception on the tax amnesty’s system, the credibility level of legal system and law, the willingness of taxpayers into the tax amnesty participants.